Control quimico de la mosca de la semilla, Delia platura (Meig.)(Dip., Anthomyiidae), en porotos - Quiroz E, C.
(En, Es)
Ilus., 12 ref.
Keywords: DELIA PLATURA; INSECTA; FRIJOL (PHASEOLUS); CONTROL QUIMICO; INSECTICIDAS; CHILE; MOSCA DE LA SEMILLA; POROTO; AGRICULTURA TECNICA